The Use of Quasi-experimental Designs for Vaccine Evaluation - Lopez Bernal, James A; Andrews, Nick; Amirthalingam, Gayatri (Clinical infectious diseases, 2019)
Randomized, controlled trials are not always possible to evaluate interventions targeting infectious disease. This is frequently the case when evaluating the population-level impact of vaccines or when evaluating interventions aiming to increase vaccine uptake. Under such circumstances, an array of quasi-experimental designs is increasingly being used to evaluate the effects of vaccines on a wide range of morbidity and health service outcomes. These studies can provide valuable information on the impact of vaccination programs and other related interventions in real-world settings. Nevertheless, not all quasi-experimental designs are equal, and it is important that authors and readers are aware of their relative strengths and potential sources of bias. In this paper, we discuss what a quasi-experimental design is, when they might be used for vaccine evaluation, their strengths and limitations, and examples of their application.